Balance Adaptation While Standing on a Compliant Base Depends on the Current Sensory Condition in Healthy Young Adults - Sozzi, Stefania; Schieppati, Marco (Frontiers in Human Neuroscience, 2022)
Background:  Several investigations have addressed the process of balance adaptation to external perturbations. The adaptation during unperturbed stance has received little attention. Further, whether the current sensory conditions affect the adaptation rate has not been established. We have addressed the role of vision and haptic feedback on adaptation while standing on foam. Method:  In 22 young subjects, analysis of geometric (path length and sway area) and spectral variables (median frequency and mean level of both total spectrum and selected frequency windows) of the oscillation of the centre of feet pressure (CoP) identified the effects of vision, light-touch (LT) or both in the anteroposterior (AP) and mediolateral (ML) direction over 8 consecutive 90 s standing trials. Results: Adaptation was obvious without vision (eyes closed, EC) and tenuous with vision (eyes open, EO). With trial repetition, path length and median frequency diminished with EC (p < 0.001) while sway area and mean level of the spectrum increased (p < 0.001). The low- and high-frequency range of the spectrum increased and decreased in both AP and ML directions, respectively. Touch compared to no-touch enhanced the rate of increase of the low frequency power (p < 0.05). Spectral differences in distinct sensory conditions persisted after adaptation. Conclusion: Balance adaptation occurs during standing on foam. Adaptation leads to progressive increase in amplitude of the lowest frequencies of the spectrum and concurrent decrease in the high frequency range. Within this common behaviour, touch adds to its stabilizing action a modest effect on adaptation rate. Stabilization is improved by favouring slow oscillations at the expense of sway minimization. These findings are preliminary to investigations of balance problems in persons with sensory deficits, ageing and peripheral or central nervous lesion.